NATURE, CHARACTERISTICS AND INSTITUTIONAL BASIS OF TURKEY'S EXPERIENCE IN ENSURING FOOD SECURITY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This article examines current food safety reforms in Turkey, covering broad economic and social goals such as improving food safety regulations and capacity, reducing supply chain losses, preventing waste, and regulating markets.